Upaya Peningkatan Kemampuan Motorik Kasar Anak Usia Dini Melalui Permainan Tradisiona di RA Al-Hidayah - Sasaudah (Education Reserach Center, 2025)
This study aimed to improve the gross motor skills of early childhood learners at RA Al-Hidayah through the use of traditional games as an active and developmentally appropriate learning approach. Conducted using a two cycle Classroom Action Research (CAR) design, the study involved 15 children aged 5–6 years. Data were obtained through observation, performance tests, and documentation, and analyzed using descriptive quantitative methods. Results showed a substantial increase in gross motor performance. Initially, only 20% of the children achieved the “good” category, while 46.7% were in the “poor” category. After Cycle I, the “good” category rose to 46.7%, and in Cycle II, following improvements in instructions, game variations, and motivation, mastery reached 80%, with no children remaining in the “poor” category. The study concludes that traditional games such as engklek, jump rope, and gobak sodor are effective in enhancing balance, agility, coordination, and gross motor strength. Additionally, these games support active, participatory learning and contribute to the preservation of local cultural heritage.